1996
DOI: 10.1182/blood.v88.6.1944.bloodjournal8861944
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil selectively spares acute myeloid leukemia cells with long- term growth abilities in immunodeficient mice and in culture

Abstract: A subset of leukemic cells is assumed to maintain long-term growth of acute myeloid leukemia (AML) in vivo. Characterization of these AML progenitor cells may further define growth properties of human leukemia. In vitro incubations with 5-fluorouracil (5-FU) have been used for enrichment of normal primitive hematopoietic stem cells. By analogy to normal hematopoiesis, it was hypothesized that primitive leukemic stem cells might be kinetically more inactive than colony- forming cells (colony-forming units-AML [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 17 publications
1
43
0
1
Order By: Relevance
“…Data from the CAFC assay revealed both short-and long-term growth capacity of leukaemic cells and also differences in proliferative activity between the subsets, confirming the heterogeneity in the clonogenic cell population (Table II). This heterogeneity was also demonstrated in human AML bone marrow using the CAFC-assay (Terpstra et al, 1996a, b). The malignant cell population of AML is maintained by a small fraction of clonogenic cells (Griffin & Lowenberg, 1986).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Data from the CAFC assay revealed both short-and long-term growth capacity of leukaemic cells and also differences in proliferative activity between the subsets, confirming the heterogeneity in the clonogenic cell population (Table II). This heterogeneity was also demonstrated in human AML bone marrow using the CAFC-assay (Terpstra et al, 1996a, b). The malignant cell population of AML is maintained by a small fraction of clonogenic cells (Griffin & Lowenberg, 1986).…”
Section: Discussionmentioning
confidence: 80%
“…Although it has been shown that the expression of CD34 does not necessarily correlate with long-term leukaemia-initiating capacity (Terpstra et al, 1996b), it is generally regarded to be associated with an immature phenotype (Lapidot et al, 1994). Furthermore, it could be shown that CFU-AML subsets were eliminated after a 5-FU treatment without affecting the late-appearing CAs (Terpstra et al, 1996a). The persistent cell population was still capable of initiating leukaemia in SCID mice, indicating a correlation between long-term leukaemia-initiating capacity and late-appearing CAs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cycle status of AML progenitor cells AML progenitor cells, like their counterparts in normal haemopoiesis, have been shown to be quiescent and resistant to chemotherapeutic drugs (Terpstra et al, 1997;Guzman et al, 2001). AML progenitor cells have been shown to be resistant to treatment with 5-FU, as the treated cells subsequently engrafted SCID mice and proliferated for over 6 weeks in a cobblestone area forming cell assay, indicating that a population of AML progenitor cells are in a quiescent (G 0 ) state (Terpstra et al, 1996b). Guzman et al (2001) used flow cytometric assays with surface, intracellular and DNA (SID) labelling to assess the cycling status of AML patients and found that 83% of CD34 þ /CD38 -/CD123 þ cells were in G 0 .…”
Section: Acute Myeloid Leukaemiamentioning
confidence: 99%
“…It is likely that these differences are partly due to a low seeding efficiency of the human HSC in these mice (van Henrick, unpublished data). For example, in SCID mice a 5-10-fold higher engraftment with human AML cells has been reported following pre-treatment of the recipients with macrophage-depleting C12MDP liposomes (Terpstra et al, 1996a). Also, the different growth requirements of these cells may affect the apparent frequencies in NOD/SCID mice.…”
Section: Scid Mouse Assaymentioning
confidence: 99%